Kesejahteraan Karyawan dan Kepemimpinan Inklusif dengan Mediasi Orientasi Layanan terhadap Kualitas Pengalaman Pelanggan - Islamiyaqin, Relis; Winasis, Shinta (DFAME Digital Financial Accounting Management Economics Journal, 2026)
This study examines the effects of employee wellbeing and inclusive leadership on customer experience quality, with service orientation as a mediating variable. Using a quantitative approach, data were collected from frontline employees working in micro, small, and medium enterprises (MSMEs) in Purwakarta, Indonesia. A structured questionnaire was administered, and the data were analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that employee wellbeing positively influences service orientation, while inclusive leadership significantly enhances service-oriented behavior. Service orientation, in turn, has a positive effect on customer experience quality. Moreover, service orientation mediates the relationship between inclusive leadership and customer experience quality, indicating that leadership affects customer outcomes through employee behavior. These findings support the Broaden-and-Build perspective by showing that positive emotional conditions generated by inclusive leadership are transformed into customer-oriented service actions. The study provides theoretical insight into the psychological mechanism linking leadership and customer experience and offers practical guidance for MSME leaders seeking to improve service performance. By integrating employee wellbeing into service management models, this research highlights the strategic importance of internal work conditions for achieving superior customer experiences.